Building collaborative competencies through play with outdoor loose parts materials in primary school. Issue 4 (4th July 2022) - Mackley, Honor; Edwards, Susan; Mclean, Karen; Cinelli, Renata
ABSTRACT: This paper reports on the findings from a study investigating the provision of outdoor loose parts materials for upper primary school aged children. Conducted in Queensland, Australia, the study focused on loose parts materials as cultural tools, following the sociocultural argument that tools mediate activity and outcomes. The findings suggest that loose parts materials are used by children in the formation of sociodramatic play, including episodes of trading, bartering and advertising that support their shared understandings. Shared understandings precede collaborative competencies, including engagements with others, working towards and achieving common goals. With collaboration recognised as an important learning disposition for children in twenty-first-century societies, the findings suggest loose parts materials may be pedagogically appropriate for supporting these competencies in primary school settings.